2022
DOI: 10.1097/aud.0000000000001240
|View full text |Cite
|
Sign up to set email alerts
|

Audiovestibular Consequences of Congenital Cytomegalovirus Infection: Greater Vulnerability of the Vestibular Part of the Inner Ear

Abstract: Objectives: To investigate the impact of congenital cytomegalovirus infection on cochlear and vestibular function.Design: This retrospective study conducted between March 2014 and March 2020 included children with confirmed congenital cytomegalovirus infection who underwent a complete audio-vestibular evaluation. It included a bithermal caloric test, a video head impulse test and a cervical vestibular evoked myogenic potential associated with a complete hearing assessment. Results:The cohort of 130 children in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 39 publications
2
13
0
1
Order By: Relevance
“…Identifying predictive factors for vestibular dysfunction to enable a targeted approach could therefore markedly increase the feasibility of vestibular evaluation in the large cCMV‐population. Various studies have previously shown that vestibular dysfunctions more commonly occur in patients with SNHL compared to normal‐hearing patients 12,13,17,19 . This was also confirmed by our results, the odds for vestibular impairment in children with SNHL at birth being 6 times higher compared to normal‐hearing children.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Identifying predictive factors for vestibular dysfunction to enable a targeted approach could therefore markedly increase the feasibility of vestibular evaluation in the large cCMV‐population. Various studies have previously shown that vestibular dysfunctions more commonly occur in patients with SNHL compared to normal‐hearing patients 12,13,17,19 . This was also confirmed by our results, the odds for vestibular impairment in children with SNHL at birth being 6 times higher compared to normal‐hearing children.…”
Section: Discussionsupporting
confidence: 91%
“…This approach is also in line with the ideal of the Vestibular Infant Screening—Flanders project (VIS‐Flanders), a recent initiative in our country in which vestibular screening is provided for children with confirmed permanent hearing loss after refer on the neonatal hearing screening 42–44 . Unfortunately, this approach seems insufficient for the cCMV‐population, as vestibular function is not necessarily safeguarded in normal‐hearing cCMV‐children 8,12,13,16,19 . Although the risk is considerably lower, the number of normal‐hearing cCMV‐patients is much higher than the number of hearing‐impaired cCMV‐patients.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Overall, compared to children with symptomatic cCMV, neurodevelopmental and other sequelae are uncommon in children with asymptomatic cCMV, particularly in children with no evidence of SNHL prior to 2 years of age [37]. Increasingly, vestibular dysfunction with visual and balance disorders are being reported in children with symptomatic and asymptomatic cCMV with and without hearing loss [38,39 ▪ ,40 ▪ ].…”
Section: Managementmentioning
confidence: 99%